When is offset not offset? When it's Australia’s defence policy for industry participation - Matthews, Ron; Fritriani (Asian Press Group Pte Ltd, 2022)
Defence offset is a controversial subject, attracting heated debate by policymakers, industrialists, and academics alike. Offset forms part of an acquisition programme and occurs because of the leverage a customer country can exert on overseas defence contractors to transfer technology and skill-intensive work. The leverage arises due to the existence of what is termed a defence buyers’ market, characterised by a paucity of high value sales opportunities and thus a preparedness by vendors to offer concessions to win orders.